Simulated galactic cosmic ray exposure activates dose-dependent DNA repair response and down regulates glucosinolate pathways in arabidopsis seedlings - Dixit, Anirudha R.; Meyers, Alexander D.; Richardson, Brian; Richards, Jeffrey T.; Richards, Stephanie E.; Neelam, Srujana; Levine, Howard G.; Cameron, Mark J.; Zhang, Ye (Frontiers in Plant Science, 2023)
Outside the protection of Earth's magnetic field, organisms are constantly exposed to space radiation consisting of energetic protons and other heavier charged particles. With the goal of crewed Mars exploration, the production of fresh food during long duration space missions is critical for meeting astronauts' nutritional and psychological needs. However, the biological effects of space radiation on plants have not been sufficiently investigated and characterized. To that end, 10-day-old Arabidopsis seedlings were exposed to simulated Galactic Cosmic Rays (GCR) and assessed for transcriptomic changes. The simulated GCR irradiation was carried out in the NASA Space Radiation Laboratory (NSRL) at Brookhaven National Lab (BNL). The exposures were conducted acutely for two dose points at 40 cGy or 80 cGy, with sequential delivery of proton, helium, oxygen, silicon, and iron ions. Control and irradiated seedlings were then harvested and stabilized in RNAlater at 3 hrs. post irradiation. Total RNA was isolated for transcriptomic analyses using RNAseq. The data revealed that the transcriptomic responses were dose-dependent, with significant upregulation of DNA repair pathways and downregulation of glucosinolate biosynthetic pathways. Glucosinolates are important for plant pathogen defense and for the taste of a plant, which are both relevant to growing plants for spaceflight. These findings fill in knowledge gaps of how plants respond to radiation in beyond-Earth environments.